Etiology and Risk Factors for Strokes in the Pediatric Population - Lidia Bartoszek; Wojciech Kapłan; Jan Ostański; Karolina Zalewa; Dominika Orłowska; Rafał Świdziński; Bartosz Skorupski; Jakub Lipiec; Monika Rogowska; Joanna Olszak (Kazimierz Wielki University, 2024)
Pediatric arterial ischemic stroke (AIS) and hemorrhagic stroke represent a relatively uncommon yet significant source of neurological challenges for neonates and children, resulting in outcomes such as hemiparesis, intellectual disabilities, and epilepsy. The etiology of pediatric strokes differs from the typical causes seen in adult stroke cases. Therefore, understanding the specific risk factors associated with strokes in children is crucial for facilitating early diagnosis, which regrettably remains frequently delayed. AIS incidence varies due to factors such as patient age, types of cerebral vascular diseases, other chronic conditions and geographic location. In this comprehensive review, we delve into the epidemiology, clinical manifestation and risk factors linked to arterial ischemic stroke and hemorrhagic stroke in neonates and children.